Use of Mobile Devices by Library and Information Science Students in Central Universities of Uttar Pradesh - Sharma, Rajul; Madhusudhan, Margam (DESIDOC Journal of Library & Information Technology, 2017)
This paper provides an insight of actual use of mobile devices by into LIS students’ in everyday life and their perceptions regarding the usefulness and effectiveness of mobile phones for academic purpose in Central universities in Uttar Pradesh state, India. The findings of the study reveal that most of the respondents use mobile devices daily for more than 3 hours. Smart phone is the most used mobile device. Respondents use productivity tools on their mobile device for creating documents. Gmail app, Whatsapp, google app, adobe reader and PDF viewer are the most frequently used mobile apps. Most of the respondents access Library Website through their mobile device and only 1.96% are accessing e-books from their mobile device. Major barriers found are: use of mobile devices for academic learning in the poor network coverage, high charging data plans, slow load time and lack of Internet speed. The findings of the study will not only guide LIS students in effective use of mobile devices for academic purposes, but will also help mobile manufactures, university authorities, librarians in exploring mobile devices adoption and usage among the respondents.